Combined spectroscopy and intensity interferometry to determine the distances of the blue supergiants P Cygni and Rigel. Issue 1 (15th June 2022) - de Almeida, E S G; Hugbart, M; Domiciano de Souza, A; Rivet, J-P; Vakili, F; Siciak, A; Labeyrie, G; Garde, O; Matthews, N; Lai, O; Vernet, D; Kaiser, R; et al.
ABSTRACT: In this paper, we report on spatial intensity interferometry measurements within the Hα line on two stars: the Luminous Blue Variable supergiant P Cygni and the late-type B supergiant Rigel. The experimental setup was upgraded to allow simultaneous measurement of two polarization channels, instead of one in our previous setup, and the zero baseline correlation function on-sky to validate independent estimates obtained from the stellar spectrum and the instrumental spectral throughput. Combined with simultaneous spectra measurements and based on radiative transfer models calculated with the code CMFGEN, we were able to fit our measured visibility curves to extract the stellar distances. Our distance determinations for both P Cygni (1.61 ± 0.18 kpc) and Rigel (0.26 ± 0.02 kpc) agree very well with the values provided by astrometry with the Gaia and Hipparcos missions, respectively. This result for Rigel was obtained by adopting a stellar luminosity of L ⋆ = 123 000 L⊙, which is reported in the literature as being consistent with the Hipparcos distance to Rigel. However, due to the lack of consensus on Rigel's luminosity, we also explore how the adoption of the stellar luminosity in our models affects our distance determination for Rigel. In conclusion, we support, in an independent way, the distance to Rigel as the one provided by the Hipparcos mission, when taking the luminosity of 123 000 L⊙ at face value. This study is the first successful step towards extending the application of the Wind Momentum Luminosity Relation method for distance calibration from an LBV supergiant to a more normal late-type B supergiant.